Serological evidence of SARS-CoV-2 infection in pets naturally exposed during the COVID-19 outbreak in Argentina - Panei, Carlos Javier (2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent of coronavirus disease 2019 (COVID-19), has rapidly spread worldwide. The monitoring of animals has shown that certain species may be susceptible to be infected with the virus. The present study aimed to evaluate the presence of SARS-CoV-2 antibodies by ELISA and virus neutralization (VN) in pets from owners previously confirmed as COVID-19-positive in Argentina. Serum samples of 38 pets (seven cats and 31 dogs) were obtained for SARS-CoV-2 antibody detection. Three out of the seven cats and 14 out of the 31 dogs were positive for SARS-CoV-2 by ELISA, and one cat and six dogs showed the presence of neutralizing antibodies in which the cat and two of the six dogs showed high titers. Another dog from which three serum samples had been obtained within eight months from the diagnosis of its owner showed the presence of antibodies at different times by both ELISA and VN. However, the results showed that the antibodies decreased slightly from the first to the third sample. Our results provide evidence that SARS-CoV-2 infection in pets living with COVID-19-positive humans from Argentina during the outbreak of SARS-CoV-2 can be detected by serology assay.